Penerapan Logika Fuzzy Metode Sugeno dalam Penentuan Harga Jual Tas Pria Branded - Zakrimal Zakrimal (Prosiding, 2023)
In today’s development, one of the things that is vast in demand is fashion, one of the fashion is a bag. From various groups, such as the lower class, middle class or upper class, men or women of all ages often use bags. The function of the bag itself is to place items and even support one’s appearance. CV Osric Sebastian is one of the few fashion bag distributors located in Batam, which started its bussiness in selling fashion bags since 2010. With the increasing need for the bags, there has been a lot of competition among bag distributors that competing with each other. Market competition among entrepreneurs will arise if the types of products produced and sold have similar types of models. The fashion bag industry itself must be able to sell products that compete in the market. One of the serious decisions that must be taken in making a sale is determining the value of the sale price of a product. The intend of this research was to determine the value of selling price of fashion bags at CV Osric Sebastian using the Sugeno fuzzy logic method. The final result of this research will be in the form of output selling price value of a fashion bag for the company based on the rules that have been made in the MATLAB program. From the results of fuzzy logic testing on the determination of the selling price of fashion bags on the system that was made can facilitate the company in making decisions to determine the value of the selling price of fashion bags at CV Osric Sebastian.